Safety management and safety outcomes in oil and gas industry in Malaysia: Safety compliance as a mediator. (1st February 2022) - Ajmal, Muhammad; Isha, Ahmad Shahrul Nizam; Nordin, Shahrina Md; Rasheed, Saba; Al‐Mekhlafi, Al‐Baraa Abdulrahman; Naji, Gehad Mohammad Ahmad
Abstract: The purpose of this study was to know the mediating role of safety compliance between safety management and safety outcomes in Malaysia's oil and gas industry. The cross‐sectional survey utilized a quantitative method for survey design. The data were collected through the convenience sampling technique via email from operation and production departments employees of the downstream sector. The analysis of 280 responses proved that safety compliance plays a significant role in enhancing safety outcomes and reducing occupational accidents and occupational injuries. Therefore, this study is helpful for practitioners to understand the importance of safety compliance and also safety management indicators in safety‐sensitive organizations, for example, the oil and gas industry of Malaysia. Furthermore, by filling the existing research gap, this study also provides fertile ground for future research and broad implications for the research industry.